Jersey : Crown Dependency of the United Kingdom; Assessment of the Supervision and Regulation of the Financial Sector Volume II-Detailed Assessment of Observance of Standards and Cod. (IMF Staff Country Reports; Country Report ;, 2003)
This report reviews the assessment of Jersey's compliance with the Basel core principles for effective banking supervision based on the Core Principles. It provides a detailed assessment of the antimoney laundering and combating the financing of terrorism regime of Jersey and reviews its laws and regulations, supervisory and regulatory systems, Jersey's compliance with the International Association of Insurance Supervisors (IAIS) insurance core principles, and benchmarks the state of insurance supervision. It also analyzes the objectives and principles of securities regulation and provides a detailed assessment of trust and company service providers in Jersey.